Densidade técnica e especialização regional produtiva: as dinâmicas de produção de celulose no Vale do Paraíba Paulista - Eskinazi, Bruna Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The spatial analyzes produced in recent years started to incorporate concepts that express not only one dimension of objects and their anchorages and existence on the territory, but linked these concepts to dimensions that result in the understanding of social and productive relations and their transformations in the work environment and of the social reproduction. For example, the concept of technical density contains the explanatory capability when involving not only the objects and the production processes, but mainly their ability to produce and to transform social relations of production. In this context of the cellulose production in Jacarei, their techniques and dynamics in the productive structure cause changes in regional production matrix, resulting from the primary production specialization. And they also deepen the homogenization processes of the territory, changing in breadth and depth the social relations of production and reproduction. Considering that the forms of the composition of the territory, which are fundamental expressions of the determination of the power relations and their clashes between distinct political projects and socio-spatial practices, they also determine degrees and/or patterns of technical density that are also differentiated. It is a process that is accomplished forward the capabilities of determining internal policies of resistance or of logical subordination to the market models. It is a process that is not only established at the level of the relations between the company and the territory, but, mainly, between the company and the society, in all its institutions, considering the socio -spatial developments that this relationship engenders

As análises espaciais produzidas nos últimos anos passaram a incorporar conceitos que expressam não apenas uma dimensão de objetos e sua fixação e existência sobre o território, mas vincularam a estes conceitos dimensões que resultam no entendimento das relações sociais e produtivas e suas transformações no âmbito do trabalho e da reprodução social. O conceito de densidade técnica, por exemplo, carrega esta capacidade explicativa ao envolver não apenas os objetos e processos produtivos, mas principalmente sua capacidade de engendrar e transformar relações sociais de produção. Neste contexto, no caso da produção de celulose em Jacareí, suas técnicas e dinâmicas na estrutura produtiva, causam transformações na matriz produtiva regional, decorrentes da especialização produtiva primária. E também, aprofundam processos de homogeneização do território, alterando em amplitude e profundidade as relações sociais de produção e de reprodução. Considerando que as formas de composição do território, expressões fundamentais da determinação das relações de poder e seus embates entre projetos políticos e práticas sócio-espaciais distintas, determinam também graus e ou padrões de densidade técnica também diferenciados. Um processo que se realiza frente às capacidades de determinação de políticas internas de resistência e ou de lógicas de subordinação aos modelos de mercado. Um processo que não se estabelece unicamente no plano das relações entre empresa e território, mas, sobretudo, empresa e sociedade, no conjunto de suas instituições, considerando os desdobramentos sócioespaciais que tal relação engendra
Keywords: Geografia econômica; Geografia agrícola; Celulose; Relações humanas; Metodologia